El desarrollo económico local y su vínculo con la innovación social: su competitividad hacia un espacio de desarrollo endógeno (Tema Central) - Lucero Mora, Giovanni Francisco (2025)
The purpose of this article is to address the relationship between local economic development (LED) and social innovation, reflecting on how these concepts have been interconnected through an evolutionary process, which allows strengthening the endogenous development of a community or region. LED is a new challenge for today’s societies, and its link with systemic competitiveness has led to a reorientation of development models. It highlights the drive for sustainable economic growth and improved quality of life in a community. It also explores the importance of culture in local development and the strengthening of social capital to promote the concept of endogenous development. It is highlighted as a reorganization process that starts from invention in the social sphere and is based on collaboration and interactive learning among social actors.